Testing housing markets for episodes of exuberance: Evidence from different Polish cities - Janusz Sobieraj; Dominik Metelski (Journal of Risk and Financial Management, 2021)
In the study we use the right-tail unit root test to analyse the presence of mild explosive dynamics (exuberance) in housing prices of the 17 largest Polish cities in the period 2006-2021 (for quarterly data). In terms of real prices from the secondary market, we were able to demonstrate the existence of episodes of mild explosive dynamics for 13 of the 17 cities studied. When we changed the context of the study and performed the same tests for the price-to-income ratio, we found that episodes of price exuberance could be indicated only in the case of two cities. The overall conclusion is that rising average incomes tend to mitigate the explosive dynamics and change the context in which the whole issue of housing bubbles is viewed. The answer to the question of whether there is indeed already a situation of price bubbles in local housing markets in Poland is of course crucial for those interested in buying or selling a housing unit (i.e., the participants of this market), but it must also remain important for the monetary authorities implementing monetary and macroprudential policies in Poland.
Keywords: 330; generalised sup augmented Dickey-Fuller (GSADF); housing bubbles; housing prices; mild explosive time series; Polish housing market; right-tailed unit root tests; supremum augmented Dickey-Fuller (SADF)